Art of the arms deal: Reagan, AWACS, and the rhetorical presidency. Issue 3 (3rd July 2019) - Fowler, Randall
ABSTRACT: During his first year in office President Reagan sought to authorize the sale of the Airborne Warning and Control System (AWACS), an advanced weapons system, to Saudi Arabia over strong congressional opposition. The Reagan administration employed a range of strategies to ensure congressional approval of the deal, including tactics of deferring and promoting and rhetorically leveraging the presidential office. By overtly breaking from Jimmy Carter's rhetoric of arms control, Reagan's rhetoric reconstituted the bounds of accepted political action regarding conventional arms transfers, in the process setting new precedents in presidential rhetoric, US–Saudi relations, and the discourse of arms control.